Pengaruh Penerapan Heptagon Fraud Theory Terhadap Kecurangan Laporan Keuangan - Raden Galang Damarjati; Retno Yulianti (Yayasan Literasi Ilmiah Indonesia, 2025)
Purpose: The pusposes of this research are to find empirical evidence of the influence of pressure, opportunity, rationalization, capability, arrogance, ignorance, and greed Method: The method of this research uses quantitative method and the sampling method uses purposive sampling method. The population in this research is non-financial State-Owned Enterprises listed on the IDX in the 2018-2023 period. It obtained 20 companies and containing 120 observation data. The data analysis technique used in this study is logistic regression which was analyzed using IBM SPSS software version 26. Finding: The results of this research are pressure which proxied by external pressure have a positive effect on financial statement fraud. Meanwhile, opportunity, rationalization, capability, arrogance, ignorance, and greed doesn’t have effect on financial statement fraud. Novelty: In previous research, the researches focus on hexagon fraud theory which amount of 6 (six) elements that cause someone to commit fraud. In this research, the researches develop into heptagon fraud theory which amount of 7 (seven) elements that cause someone to commit fraud. This research develop fraud detection methods who used by (Pamungkas & Irwandi, 2024) and (Satata et al., 2024) which still use Beneish M-Score model. This research uses the F-Score model which is a development of the formula from the Beneish M-Score.